2014
DOI: 10.1002/pon.3732
|View full text |Cite
|
Sign up to set email alerts
|

Emotional distress in parents of long-term survivors of childhood acute lymphoblastic leukemia

Abstract: Objective The current study investigated the occurrence of emotional distress in parents of long-term survivors of childhood acute lymphoblastic leukemia (ALL) and identified factors associated with parent emotional distress symptoms. Methods Parents of 127 long-term survivors of childhood ALL treated on a chemotherapy-only protocol at St. Jude Children’s Research Hospital participated in the study. Parents completed standard ratings of emotional distress, caregiver strain, and child physical, emotional, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 35 publications
3
32
0
3
Order By: Relevance
“…In addition, psychosocial family risk was negatively associated with both parent-proxy and child self-reported hrql. These findings are consistent with previous literature that has found that parent distress is associated with lower parent-reported child hrql in children on active treatment 13,16 . One possibility for the lack of relation between parental distress and child-reported hrql may be due to differences in parent and child perceptions of the child's hrql.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, psychosocial family risk was negatively associated with both parent-proxy and child self-reported hrql. These findings are consistent with previous literature that has found that parent distress is associated with lower parent-reported child hrql in children on active treatment 13,16 . One possibility for the lack of relation between parental distress and child-reported hrql may be due to differences in parent and child perceptions of the child's hrql.…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, previous findings have shown that high levels of parent distress symptoms are positively associated with the distress symptoms of pediatric cancer survivors 13 . Indeed, the association between parent and child distress has been shown to become stronger over time following a child's diagnosis, making this association particularly poignant as the child transitions to survivorship 14,15 .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, emotional discuss such as PTSS can persist many years following the completion of therapy . Parental distress has been associated with their report of emotional symptoms in child survivors of ALL, although it is unclear whether this distress impacts the child's emotional or behavioral symptoms . The association between parental emotional distress or PTSS and behavioral problems in childhood cancer survivors requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…There have been inconsistent reports pertaining to emotional distress in parents of survivors of childhood cancer, 8 Most parents of survivors of ALL treated on chemotherapy-only protocols do not have elevated symptoms of anxiety, depression or post-traumatic stress symptoms (PTSS); however subgroups of parents do report substantial symptoms of psychological distress or PTSS. 8,9 Furthermore, emotional discuss such as PTSS can persist many years following the completion of therapy. 10 Parental distress has been associated with their report of emotional symptoms in child survivors of ALL, although it is unclear whether this distress impacts the child's emotional or behavioral symptoms.…”
Section: Introductionmentioning
confidence: 99%